2013
DOI: 10.1016/j.margeo.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic characterization of the U.S. Atlantic continental margin

Abstract: The increasing volume of multibeam bathymetry data collected along continental margins is providing new opportunities to study the feedbacks between sedimentary and oceanographic processes and seafloor morphology. Attempts to develop simple guidelines that describe the relationships between form and process often overlook the importance of inherited physiography in slope depositional systems. Here, we use multibeam bathymetry data and seismic reflection profiles spanning the U.S. Atlantic outer continental she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 57 publications
0
53
0
Order By: Relevance
“…Previous studies on the U.S. Atlantic margin suggested that regional slope gradient does not necessarily correlate with landslide occurrence (e.g., Twichell et al, 2009 slope gradient and basic margin physiography have profound influences on depositional processes and the accumulation patterns of potentially unstable depocenters (Brothers et al, 2013a). Other factors such as weak layers, pore-fluid overpressures, and bottom stress (both transient and by salt tectonics) may also influence slope stability.…”
Section: Conditions That Contribute To Slope Failuresmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies on the U.S. Atlantic margin suggested that regional slope gradient does not necessarily correlate with landslide occurrence (e.g., Twichell et al, 2009 slope gradient and basic margin physiography have profound influences on depositional processes and the accumulation patterns of potentially unstable depocenters (Brothers et al, 2013a). Other factors such as weak layers, pore-fluid overpressures, and bottom stress (both transient and by salt tectonics) may also influence slope stability.…”
Section: Conditions That Contribute To Slope Failuresmentioning
confidence: 96%
“…Limited accommodation space during former sea level lowstands, and the proximity of the shelf edge to the steep upper continental slope (Brothers et al, 2013a) led to considerable sediment bypass to the lower slope. Poag (1992) estimated the volume of Pleistocene sediments on the shelf and upper slope to be 5% of the total sediments delivered to the margin and the volume of Pliocene sediments to be 10% of the total.…”
Section: Conditions That Contribute To Slope Failuresmentioning
confidence: 99%
See 3 more Smart Citations